Career Development Interventions for Social Justice: Addressing Needs across the Lifespan in Educational, Community, and Employment Contexts - Jackson, Margo A.; Regis, Allyson K.; Bennett, Kourtney (Rowman & Littlefield Publishers, 2019)
Keywords: dept.sa

Academic support and college success for postsecondary students with learning disabilities - Troiano, P.F.; Liefeld, J.A.; Trachtenberg, J.V. (Journal of College Reading and Learning, 2010)
The relationship between degree of academic support center use and college success was examined in a population of 262 college students with learning disabilities. Five years of attendance data and graduation rates were examined and submitted to discriminant function analysis to evaluate the predictive influence of academic support center use on college student outcomes. Results indicated that students who had higher levels of attendance in an academic support center had higher overall grade point averages and higher rates of graduation. That is to say, students with learning disabilities who attended learning support centers regularly were more likely to have higher grades and graduate college than those who did not. © 2010, College Reading and Learning Association.
Keywords: dept.sa; peer-reviewed